2014
DOI: 10.1074/jbc.m113.521336
|View full text |Cite
|
Sign up to set email alerts
|

AKT and GSK-3 Are Necessary for Direct Ezrin Binding to NHE3 as Part of a C-terminal Stimulatory Complex

Abstract: Background: Phosphoinositides and ezrin form a complex with NHE3, which stimulates basal transport activity. How this complex is regulated is unknown. Results: GSK-3 and Akt stimulate NHE3 activity by changing ezrin binding. Conclusion: Sequential effects of two kinase regulate the association of NHE3 with ezrin to affect basal activity. Significance: A novel Ser cluster in the NHE3 C-terminal domain regulates its ezrin binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…However, since only a 13% reduction of CHP binding was demonstrated, cause and effect has not been established. In addition, this stimulatory signaling complex involves direct binding of ezrin to NHE3 amino acids 517, 521, and 528, which requires phosphorylation of amino acids 516 and 527 (human NHE3) by Akt and GSK-3, respectively, as well as CHP binding (38). This ezrin binding to NHE3 is required not only for basal NHE3 activity but for multiple examples of stimulated NHE3 activity, and it is possible that ezrin binding is disrupted by this polymorphism to explain the failure of dexamethasone to stimulate NHE3.…”
Section: C762mentioning
confidence: 99%
See 1 more Smart Citation
“…However, since only a 13% reduction of CHP binding was demonstrated, cause and effect has not been established. In addition, this stimulatory signaling complex involves direct binding of ezrin to NHE3 amino acids 517, 521, and 528, which requires phosphorylation of amino acids 516 and 527 (human NHE3) by Akt and GSK-3, respectively, as well as CHP binding (38). This ezrin binding to NHE3 is required not only for basal NHE3 activity but for multiple examples of stimulated NHE3 activity, and it is possible that ezrin binding is disrupted by this polymorphism to explain the failure of dexamethasone to stimulate NHE3.…”
Section: C762mentioning
confidence: 99%
“…This regulation involves both increased and reduced NHE3 activity, as occurs sequentially after meals. Mutations in this region lead to dysregulation of NHE3 to physiological activators or inhibitors (27,38,44).…”
mentioning
confidence: 99%
“…This motif is present in the Pro-rich sequence of L-type GATA-6 ( 32 PSTP and 35 PPSP). Phosphorylation of the C-terminal Ser-rich sequence motif of the Na + /H + exchanger (NHE3) by Akt and GSK-3 stimulates NHE3 activity through Ezrin binding to this motif [26]. The consensus sequence for the GSK-3 substrate (S/T)XXX(S/T) is also present in the Pro-rich segment and the Ser-cluster of L-type GATA-6 ( 33 STPPS 37 and 40 SSSSSS 45 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This regulatory effect requires amino acids at its C-terminal to interact with the CaMKII binding domain downstream of NHE3 aa 690 (Ser693, Ser694, and Ser810), which is part of the putative CaMKII phosphorylation consensus sequence [45,46]. Recently, it was demonstrated that 1) NHE3 basal activity is regulated by a signaling complex that is controlled by the sequential effects of two kinases, Akt and GSK-3, which act on a Ser cluster in the same NHE3 C-terminal domain that binds ezrin, and 2) these kinases regulate the dynamic association between ezrin and NHE3 to affect basal NHE3 activity [9]. CaMKII is therefore generally inactive in the presence of basal levels of Ca 2+ , and active CaMKII is generally created via the autophosphorylation and release of the kinase sequence from the CaMKII autoinhibitory domain.…”
Section: Nhe3mentioning
confidence: 99%
“…In the nephron, individual NHE isoforms have different functions. These functions are reflected in their differential expression along the segments of the nephron, their localization in renal epithelial cells at the basolateral (e.g., isoform NHE1) or apical surface (e.g., isoform NHE3), and their activation in response to distinct agonists [4][5][6][7][8][9][10][11][12][13].…”
Section: Nhementioning
confidence: 99%